Penegakan Hukum oleh Ditreskrimsus Polda Sumatera Utara terhadap Ujaran Kebencian Menggunakan Sarana Media Sosial - Masfan Masfan; Didik Miroharjo; Alpi Sahari (Iuris Studia: Jurnal Kajian Hukum, 2021)
Law enforcement is a very important thing in the process of developing the Indonesian nation, where without law enforcement development will experience obstacles in its implementation, and the development process must be pursued to run regularly and sustainably (sustainable development) in every sector and across sectors. so that it can achieve its goal of providing protection and social welfare for all Indonesian people. The number of people in Indonesia is increasing every year. The research method used in this research is empirical juridical. The results showed that the investigators of the Ditreskrimsus Polda of North Sumatra determined the status of the reported party as a suspect in the enforcement of the hate speech law after clear evidence was available. The obstacles faced by the Ditkrimsus Investigators of the North Sumatra Police in enforcing the law against hate speech using social media are: the perpetrators are public figures, are considered to curb freedom of opinion, Simcar can be used without a registration process, lack of public awareness of the prohibition of spreading hate speech, and the circulation of fake accounts, a criminal policy that can be done to prevent hate speech crimes using social media is to make a policy so that all Simcars can only be used after going through the registration process and tighten the requirements for creating social media accounts to prevent fake account.